2012
DOI: 10.3758/s13423-012-0305-z
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of the fluency–confidence association in problem solving

Abstract: Confidence in answers is known to be sensitive to the fluency with which answers come to mind. One aspect of fluency is response latency. Latency is often a valid cue for accuracy, showing an inverse relationship with both accuracy rates and confidence. The present study examined the independent latency-confidence association in problem-solving tasks. The tasks were ecologically valid situations in which latency showed no validity, moderate validity, and high validity as a predictor of accuracy. In Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 27 publications
8
77
1
Order By: Relevance
“…Procedural knowledge refers to the performing of knowledge or implicit knowledge and is a behaviour or skill. If knowing when and why to use a particular skill is important it becomes conditional knowledge which involves the regulation of memory, thought and learning (Ackerman & Zalmanov, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Procedural knowledge refers to the performing of knowledge or implicit knowledge and is a behaviour or skill. If knowing when and why to use a particular skill is important it becomes conditional knowledge which involves the regulation of memory, thought and learning (Ackerman & Zalmanov, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although no prior JOL study has used coherent and incoherent triads (but see Ackerman & Zalmanov, 2012, for a study of metacognition in problem solving), research on the effect of pair relatedness on JOLs is relevant. This work demonstrated that JOLs are higher for related than for unrelated paired associates (cf.…”
mentioning
confidence: 99%
“…Students may respond to such feelings by cheating as indicated above (Batane 2010), by giving up (Smith et al 1982), by selfhandicapping (Thompson and Hepburn 2003), or by finding ''honest'' cognitive shortcuts that enable them to feel successful despite an actual lack of progress (Chance et al 2011). Moreover, people often mistakenly associate ease (or what some researchers call fluency) with learning or knowing, and they interpret cognitive strain as a sign of stupidity or error (Bjork 1994;Dunning 2005;Ackerman and Zalmanov 2012). As a result, cognitive shortcuts that, like patchwriting, enable students to sustain their self-esteem and feel like they accomplished the task easily may seem particularly alluring.…”
Section: Why Students Take Cognitive Shortcutsmentioning
confidence: 95%